2019
DOI: 10.1055/s-0039-1693483
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Adolescent Bupropion Overdose with Intravenous Lipid Emulsion Therapy

Abstract: Bupropion overdose in the pediatric setting poses significant potential for toxicity. We present the case of a 15-year-old female patient presenting with intentional bupropion overdose resulting in generalized tonic–clonic seizures, severe acidosis, vomiting, and tachycardia after ingestion of between 1,650 to 9,000 mg (24–133 mg/kg) of bupropion. The patient was admitted to pediatric intensive care unit (PICU) where toxicity was resolved promptly following administration of intravenous lipid emulsion (ILE) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Bupropion is a common behavioral modulator used to treat depression, mood disorders, and tobacco dependence [6]. Bupropion is a synthetic norepinephrine/dopamine/serotonin reuptake inhibitor and is available in three formulations including immediate release, sustained release, and extended release [7]. Bupropion has three major bioactive metabolites, of which hydroxybupropion is the most clinically relevant [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Bupropion is a common behavioral modulator used to treat depression, mood disorders, and tobacco dependence [6]. Bupropion is a synthetic norepinephrine/dopamine/serotonin reuptake inhibitor and is available in three formulations including immediate release, sustained release, and extended release [7]. Bupropion has three major bioactive metabolites, of which hydroxybupropion is the most clinically relevant [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…3 As suggested by Bornstein et al, the lipid sink theory, which is considered the mechanism underlying the effect of lipid emulsion as a nonspecific antidote, states that lipid emulsion absorbs highly lipid-soluble drugs, such as bupivacaine (log [octanol/water partition coefficient]: 3.41), from the heart. 1,4 However, the following comments should be considered to understand this case report well. First, the first administration of lipid emulsion improved the mental status of the patient.…”
mentioning
confidence: 98%
“…We have read with interest the case report, "Successful Management of Adolescent Bupropion Overdose with Intravenous Lipid Emulsion Therapy," recently published in the Journal of Pediatric Intensive Care. 1 Lipid emulsion is effective in the treatment of acute toxicity induced by local anesthetics or nonlocal anesthetic drugs, including amitriptyline, bupropion, and verapamil, in pediatric patients. 2 A previous in vitro study reported that the magnitude of the reduction of the serum concentration of bupropion, which is a highly lipid-soluble antidepressant (log [octanol/water partition coefficient]: 3.2), was 46 by 2% lipid emulsion (Intralipid).…”
mentioning
confidence: 99%
See 2 more Smart Citations